2004
DOI: 10.1074/jbc.m406779200
|View full text |Cite
|
Sign up to set email alerts
|

The Cysteine-rich Region of T1R3 Determines Responses to Intensely Sweet Proteins

Abstract: A wide variety of chemically diverse compounds taste sweet, including natural sugars such as glucose, fructose, sucrose, and sugar alcohols, small molecule artificial sweeteners such as saccharin and acesulfame K, and proteins such as monellin and thaumatin. Brazzein, like monellin and thaumatin, is a naturally occurring plant protein that humans, apes, and Old World monkeys perceive as tasting sweet but that is not perceived as sweet by other species including New World monkeys, mouse, and rat. It has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
230
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(248 citation statements)
references
References 21 publications
8
230
0
10
Order By: Relevance
“…KO mice deficient in either Tas1r2 or Tas1r3 display profound deficits in their responses to sweeteners (11,12). Heterologous expression of the human form of T1r2 + T1r3 generates receptor activity responsive to a broad array of sweet compounds, including monosaccharide and disaccharide sugars (e.g., glucose, fructose, sucrose), sugar alcohols, small-molecule noncaloric sweeteners (e.g., saccharin, cyclamate, sucralose, aspartame, neotame), and large-molecule noncaloric sweeteners (e.g., monellin, thaumatin, brazzein) (7,(13)(14)(15)(16)(17). Heterologous expression of the rodent form of T1r2 + T1r3 generates a similarly broad-acting receptor but without activity toward the "human-specific sweeteners" (cyclamate, aspartame, neotame, monellin, and thaumatin) recognized as sweet by humans and old world primates but not by rodents.…”
mentioning
confidence: 99%
“…KO mice deficient in either Tas1r2 or Tas1r3 display profound deficits in their responses to sweeteners (11,12). Heterologous expression of the human form of T1r2 + T1r3 generates receptor activity responsive to a broad array of sweet compounds, including monosaccharide and disaccharide sugars (e.g., glucose, fructose, sucrose), sugar alcohols, small-molecule noncaloric sweeteners (e.g., saccharin, cyclamate, sucralose, aspartame, neotame), and large-molecule noncaloric sweeteners (e.g., monellin, thaumatin, brazzein) (7,(13)(14)(15)(16)(17). Heterologous expression of the rodent form of T1r2 + T1r3 generates a similarly broad-acting receptor but without activity toward the "human-specific sweeteners" (cyclamate, aspartame, neotame, monellin, and thaumatin) recognized as sweet by humans and old world primates but not by rodents.…”
mentioning
confidence: 99%
“…Every one of these three domains contains agonist binding sites, explaining sweet receptor activation by a vast repertoire of chemically distinct molecules. Sucrose and noncaloric sweeteners such as aspartame and neotame interact within the VFT of T1R2 (9,10), other noncaloric sweeteners such as cyclamate and neohesperidin dihydrochalcone (NHDC) interact within the TMD of T1R3 (10-12), S819, a synthetic sweet agonist, interacts with the TMD of T1R2 (10), and the sweet-tasting protein brazzein requires the cysteine-rich domain of human T1R3 to activate the receptor (13).…”
mentioning
confidence: 99%
“…In support of this hypothesis, Jiang et al identified 10 residues in the CRD of human T1R3 and the hinge region of T1R2 that play an important role in the effect of sweet proteins, such as brazzein [45] .…”
Section: Tm Allosteric Sitesmentioning
confidence: 83%
“…Aside from the orthosteric sites, there are at least eight allosteric sites that have been identified in taste receptors: the EDAM sites for IMP in T1R1-VFT [31] and for SE-2/SE-3 in T1R2-VFT [67] ; the allosteric agonist sites for sweet proteins in T1R3-CRD [45] , cyclamate in sweet receptor T1R3 7TM [70] , S807 in T1R1 7TM [31] and S819 in T1R2-7TM [31] ; the PAM site for cyclamate in the umami receptor T1R3-7TM [70] ; and the NAM site for lactisole in both the sweet and umami receptor T1R3-7TM [71] . These sites might represent potential targets for health-related products or drugs to treat diseases, such as hypertension or diabetes.…”
Section: Ligand Binding Sites Of Four Typical Class C Gpcr Family Memmentioning
confidence: 99%
See 1 more Smart Citation